Development of switchgear life cycle cost analysis software - Loo Y.L.; Yaw C.T.; Hashim A.H.; AMMohamad; Faizah M.K.; Noormala A. (2023)
In today's demanding business environment, determining the Life Cycle Cost Analysis (LCCA) is important in order for utilities to make the right decision when it embarks on any form of assets retrofit or refurbishment or replacement. The LCCA is a process of evaluating the economic performance of an asset over its entire life. Sometimes known as "whole cost accounting" or "total cost of ownership", LCCA balances initial monetary investment with the long-term expense of owning and operating the assets. This research has developed an LCCA model for distribution switchgears through identification, analysis and development of switchgear life cycle cost profiles, data and information sources from available assetbased and financial system in TNBD. 2010 IEEE.